3D particle‐in‐cell simulation of positive streamer initiation in highly pressurized gaseous, liquid and supercritical CO2 with field ionization. Issue 1 (27th October 2020) - Abbas, Muhammad Farasat; Yuan, Xu‐Chu; Li, Han‐Wei; Xue, Jian‐Yi; Sun, An‐Bang; Zhang, Guan‐Jun
Abstract: A 3D particle‐in‐cell/Monte Carlo collision model is used to investigate the streamer discharge inception in CO2 at elevated pressures including gaseous, liquid and supercritical phases. Generation of free electrons is a prerequisite for initiation and development of positive streamers. Field ionization from impurity molecules of low density and low ionization energy is assumed as the source of primary ionization in the model. The field dependent generation rate of electrons is calculated by Zener's model. Tree‐like streamer with filamentary shape presents at the needle tip and propagates towards the plane electrode in all three phases of CO2, with differing in length and propagation speed. Furthermore, the influence of different parameters such as applied voltage, electrode tip size, and ionizable density and ionization potential of impurity molecules on the evolution of streamer discharge in supercritical CO2 are investigated. Simulation results obtained from the 3D model agree well with experimental observations in the literature, which show that field ionization might be one of possible ionization sources in pressurized CO2 in the presence of high electric field.